IMPLEMENTASI PROYEK BUDIDAYA JAMUR TIRAM SEBAGAI PEMBELAJARAN KONTEKSTUAL DI SEKOLAH DASAR NEGERI SADARMANAH, KECAMATAN CAMPAKA MULYA, KABUPATEN CIANJUR - Amalia, Nelly; Yoseptry, Ricky; Tanti, Tanti; Diana, Nenden; Risgianti, Riscky (STKIP PGRI Situbondo, 2025)
Abstract: This study explores the implementation of an oyster mushroom cultivation project as a contextual learning model at Sadarmanah Elementary School, located in Campaka Mulya District. The objective of the project was to enhance students’ understanding of scientific and environmental concepts while simultaneously fostering practical skills, critical thinking, and character development. Using a project-based learning (PjBL) framework, students were actively engaged in every stage of the cultivation process, including planning, preparation, observation, and harvesting. Data collection methods included observation, interviews, student journals, and performance assessments. The findings reveal significant improvements in students' conceptual understanding of biology and ecosystems, as well as the development of soft skills such as collaboration, responsibility, and environmental awareness. Moreover, the project served as a bridge between classroom theory and real-life applications, aligning well with the principles of the Merdeka Curriculum and the Profile of Pancasila Students. This study suggests that contextual, environmentally-based project learning is an effective strategy to enrich learning experiences and support the holistic growth of elementary students.